THE RIGHT TO APPROPRIATE EDUCATION: PERSPECTIVES FROM TWO INCLUSIVE SCHOOLS (Proceedings of International Conference on Special Education, 2015)
This study, using the case study approach, aims to find out how two inclusive schools protect and uphold the right to have appropriate education of children with disabilities through their inclusive educational policy and processes derived from the experiences of the stakeholders in the school. With the main research question of: “To what extent that the inclusive educational programs of these two schools safeguard the right of appropriate education of children with disabilities?” Particularly, the study explored: (a)The practices and policies of the schools that enable inclusive education; (b)The experiences of the stakeholders in the right to inclusive education; (c)The innovative strategies utilized by the school administrations and teaching force in upholding the right to have ; and (d) The outcome of inclusion on the school and community culture. The partakers of the study included students with and without disabilities, school administrators, special and general education teachers, parents and caregivers. Data were analyzed and triangulated within multiple sources to ensure substantiation thus identifying discrepancies and commonalities specifically using in-depth semi-structured interviews and focus group discussions with administrators, teachers, parents and caregivers, field observations, document and archival exploration, portfolios and videotape analyses. Data analysis was done concurrently with data collection through an interactive, recursive and dynamic process and quotations were used for exposition and clarification of major themes. Findings of this study revealed accounts of significant harmony within major stakeholders at both theoretical and application levels in their journey in realizing and upholding the right to have appropriate inclusive education program for children with disabilities. Implications for future research in inclusive education are discussed